Proposal for Bioenergy Territorial Planning in LATAM; Part 1/2: Circular Economy Model, Urban Component Using Household Biomass - Gómez Montoya, Juan Pablo (2024)
The research is divided into two articles, presenting a bioenergy territorial planning proposal for LATAM. The first part focuses on an urban circular economy (CE) model using household organic municipal waste based on source separation. The second part is related to a proposal for designing internal combustion engines for renewable and alternative gaseous fuels. This paper quantifies the bioenergy potential that could be generated for LATAM by using national population censuses-based on scientific formulation and AI-powered databases to estimate the amount of biofertilizers, biogas, and green hydrogen that can be obtained according to the proposed CE model. The sustainability of the CE model is analyzed through a thermo-economic assessment, social impact, and environmental impact, with carbon footprint measurement using a standardized calculator. Additional considerations, risk analysis, and challenges for the model's implementation are also presented to promote its widespread adoption.